Pemanfaatan Case Based Reasoning sebagai Rekomendasi Produk Kamera - Wardhana, Nyoman Putra Prasetya; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
The camera is one device that is often used to capture the moment. Not everyone has a camera because it is quite difficult to operate, and the price is also relatively expensive. For beginners who want to dive into the world of photography, will definitely look for a camera that suits with their current condition. The application of the CBR algorithm will produce a list of camera recommendations according to the user's wishes. Therefore, a recommendation system with sufficient camera data is needed to facilitate the search for various types of cameras. From the results of this study obtained 5 recommendations for the best camera generated from the CBR model.